2021
DOI: 10.3390/molecules26071904
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Pyrazinamide Coordination Frameworks Synthesized by Mechanochemistry

Abstract: The urge for the development of a more efficient antibiotic crystalline forms led us to the disclosure of new antibiotic coordination frameworks of pyrazinamide, a well-known drug used for the treatment of tuberculosis, with some of the novel compounds unravelling improved antimycobacterial activity. Mechanochemistry was the preferred synthetic technique to yield novel compounds, allowing the reproduction of a 1D zinc framework, the synthesis of a novel hydrogen bonding manganese framework, and three new compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 55 publications
(40 reference statements)
0
8
0
1
Order By: Relevance
“…[85] Quaresma et al also explored the formation of metal complexes based on pyrazinamide, an antimycobacterial agent, with zinc, manganese and silver nitrates exhibiting for some 1D coordination frameworks (Scheme 33). [86] Antimicrobial activity of complexes derived from manganese and silver was found to be higher than the one of pyrazinamide. Of note, the silver complex tested resulted from a stoichiometric reaction between silver(I) nitrate and pyrazinamide and its structure could not be properly identified.…”
Section: Complexation Of Already Existing Drugsmentioning
confidence: 99%
“…[85] Quaresma et al also explored the formation of metal complexes based on pyrazinamide, an antimycobacterial agent, with zinc, manganese and silver nitrates exhibiting for some 1D coordination frameworks (Scheme 33). [86] Antimicrobial activity of complexes derived from manganese and silver was found to be higher than the one of pyrazinamide. Of note, the silver complex tested resulted from a stoichiometric reaction between silver(I) nitrate and pyrazinamide and its structure could not be properly identified.…”
Section: Complexation Of Already Existing Drugsmentioning
confidence: 99%
“…152 There are several reports on mechanochemical preparation of drug-containing metal-organic compounds. [151][152][153][154][155][156][157][158][159][160] Friščić and co-workers demonstrated that LAG methods in which water was used as grinding liquid were highly effective for the rapid and room temperature synthesis of various APIs (such as S and RS form of ibuprofen, salicylic acid or naproxen) from MgO which was previously considered an inert precursor for mechanochemical synthesis. 155,161 André group developed an effective mechanosynthesis route to construct a series of nalidixic acid-containing metal complexes and coordination polymers to overcome the low solubility of this widely used antibiotic.…”
Section: Bio-mofsmentioning
confidence: 99%
“…With pyrazinamide, an antibiotic used in the treatment of tuberculosis, NG led to the formation of four complexes with Zn(II), Mn(II), and Ag(I) [ 84 ]. By adjusting the stoichiometry of the starting materials, it was possible to obtain two different Ag(I) compounds.…”
Section: Developments Of Mechanochemistry In Portugalmentioning
confidence: 99%